Antenatal dietary and lifestyle advice for women who are overweight or obese and the effect on fetal growth and adiposity: the LIMIT randomised trial. (January 2016) - Grivell, RM; Yelland, LN; Deussen, A; Crowther, CA; Dodd, JM
Abstract : Objective: To report the influence of maternal overweight and obesity on fetal growth and adiposity and effects of an antenatal dietary and lifestyle intervention among these women on measures of fetal growth and adiposity as secondary outcomes of the LIMIT Trial. Design: Randomised controlled trial. Setting: Public maternity hospitals in metropolitan Adelaide, South Australia. Population: Pregnant women with a body mass index ≥ 25 kg/m 2, and singleton gestation between 10 +0 and 20 +0 weeks. Methods: Women were randomised to Lifestyle Advice or continued Standard Care and offered two research ultrasound scans at 28 and 36 weeks of gestation. Main outcome measures: Ultrasound measures of fetal growth and adiposity. Results: For each fetal body composition parameter, mean Z ‐scores were substantially higher when compared with population standards. Fetuses of women receiving Lifestyle Advice demonstrated significantly greater mean mid‐thigh fat mass, when compared with fetuses of women receiving Standard Care (adjusted difference in means 0.17; 95% CI 0.02–0.32; P = 0.0245). While subscapular fat mass increased between 28 and 36 weeks of gestation in fetuses in both treatment groups, the rate of adipose tissue deposition slowed among fetuses of women receiving Lifestyle Advice, when compared with fetuses of women receiving Standard Care ( P = 0.0160). No other significant differences were observed. Conclusions: These findings provide the first evidence of changes to fetal growth following an antenatal dietary and lifestyle intervention among women who are overweight or obese. Tweetable abstract: Lifestyle advice for overweight and obese pregnant women modifies fetal body composition. Tweetable abstract: Lifestyle advice for overweight and obese pregnant women modifies fetal body composition.